Inequality Of Basic Education In Indonesia: Policy Between MI And SD - Shobiroh Nia Ulfa Kurniyawati; Sutrisno Sutrisno; Irhas Badruzaman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Madrasah is the second institution that was established in the 20th century after pesantren. When viewed from a historical perspective, Islamic educational institutions (madrasas) have experienced a very long polemic until now, it seems that the polemics that madrasas go through will never end if the government does not really pay attention to the existence of madrasas in Indonesia. This research is an expression of the author's criticism of the government so that it can pay more attention to madrasas so that madrasas can develop optimally both in terms of quality of education, quality of teachers, facilities and infrastructure, student development, and so on. When we look at the development of madrasas from time to time, namely from the post-independence period to the New Order era, in fact in the Joint Decree (SKB) three ministers have emphasized that madrasas will be well cared for by the government, but the question is why until now there is still inequality. government policy on madrasah development ?. This research reveals the various gaps that exist regarding the development of madrasas in Indonesia. This research is a literature research in which the author collects references using a digital system, namely the publish or perish search engine so that thousands of relevant literature are obtained and then selected from the highest to the lowest rank and analyzed.